The Relationship Between Learning Styles with Learning Outcome and Scientific Literacy of Islamic Junior High School (MTs) Students in Mataram - Gito Hadiprayitno; A Wahab Jufri; Siti Syifa’un Nufus (Universitas Sebelas Maret, 2020)
Learning style is one of the important elements in the learning process of students. Information about student learning styles will help teachers design appropriate learning so that students can more easily absorb, organize, and process information during the learning process. Learning following the character of students in the class will create joyful learning and influences student learning outcomes and abilities, including scientific literacy. This study aims to investigate the relationship between learning styles with student learning outcomes and scientific literacy. This research is descriptive survey research. This research was conducted at MTsN 1 Mataram and MTsN 2 Mataram. The research sample was 55 MTs students in Mataram who were selected non-randomly. The variables measured were learning styles, scientific literacy skills, and science learning outcomes. Learning styles in this study consist of visual, auditory, read/write, and kinesthetic (VARK). Learning styles were measured using the VARK questionnaire which was adapted from Neil D. Fleming's version 8.01 questionnaire which can be accessed through the VARK website. Scientific literacy in this research includes indicators (a) explaining phenomena scientifically, (b) assessing and designing scientific investigations, and (c) interpreting data and evaluating scientific evidence. Science literacy data were collected using a scientific literacy test consists of 40 multiple-choice questions that spread evenly on each indicator. The test instrument used in this study has gone through a validation process by experts. The collection of data on learning styles and scientific literacy carried out online using the Google Form by asking respondents to fill out a learning style questionnaire and to answer questions on the science literacy test. Science learning outcomes data obtained from the even semester science final exam scores. Analysis of the relationship between learning styles and scientific literacy used bivariate correlation, while the analysis of the effect of learning styles on learning outcomes and scientific literacy used ANACOVA.The results of the study indicated that the trend of auditory and kinesthetic learning styles correlated significantly with students' scientific literacy (p <0.05), whereas visual and reading/writing learning styles did not significantly correlate (p> 0.05). The type of learning styles does not have a different effect on student learning outcomes and scientific literacy, but scientific literacy has a significant influence on learning outcomes (p <0.05).